Performance of Agricultural Extension Workers: The Impact of Internal and External Factors - Marsianus Falo; Ody Wolfrit Matoneng; Oktovianus Tabenu (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
This study aims to describe the internal and external characteristics of agricultural extension workers and analyze their influence on extension performance in North Central Timor Regency. A quantitative approach was employed using a survey method involving all 126 active agricultural extension workers, supplemented by qualitative data through Focus Group Discussions (FGDs) using a snowball sampling technique. Structural Equation Modeling-Partial Least Squares (SEM-PLS) was used to analyze the collected data. The results show that internal factors such as productive age, very high formal education, long working experience, high work motivation, and high income positively contribute to extension performance, while areas of expertise and training still require improvement. External factors such as the availability of facilities and access to agricultural technology were categorized as high, whereas media consumption, farmer participation, land potential, and the reward system were relatively low. The research model revealed that internal and external factors together explain 81.5% of the variance in extension performance (R² = 0.815), with an overall model fit of 96.3% (Q² = 0.963). These findings highlight the importance of enhancing areas of expertise and increasing media information consumption to strengthen agricultural extension performance in the future.